Sahel terrorist crisis and development priorities: case of financial allocations for the control of non-communicable diseases in Burkina Faso - Ouedraogo, Moussa; Sanou, Dia; Kere, Ines Wendlassida Zaheira; Sankara, Souleymane; Thiombiano-Coulibaly, Nana; Ouedraogo, Ousmane; Zoungrana, Bassibila; Hama-Ba, Fatoumata; Savadogo, Aly (Frontiers in Public Health, 2023)
In Africa, nearly 46% of all mortality will be attributed to non-communicable diseases (NCDs) by 2030. While the cost of inaction far exceeds the cost of action against NCDs, global funding for the prevention and control of NCDs is minimal. The objective of this was to explore the Ministry of Health budget allocations for NCDs from 2010 to 2020 as well as the effect of the terrorism crisis on these allocations. The methodology was based on the budget tracking tool developed by the Scaling Up Nutrition Movement. Twenty-nine budget lines related to the prevention and/or control of NCDs have been identified. About 29.9 million USD were allocated to the fight against NCDs with an absorption rate of more than 98%.There is an upward trend of allocated budget characterized by an exponential increase from the development of the national integrated strategic plan for the fight against NCDs (2016–2020). In 2017, an increase of 184% compared to 2016 was observed. However, the efforts were challenged by the emergence of the terrorist threat which triggered in January 2016, leading to a drastic reduction in allocations for NCDs in favor likely of defense and security priorities as well as addressing the needs of internally displaced persons. A trend analysis suggests that the NCDs budget significantly decrease as the country global terrorist index increase. Further analysis is needed to better understand the implication on NCD incidence, and identify advocacy opportunities for mitigating the negative impact of the terrorist treat on NCDs and other development issues.